Economic Impacts of Small Tourism Enterprises: A Case Study of Kaulepani Community Homestay (Journal of Tourism and Himalayan Adventures, 2019)
Kaulepani is one of the most beautiful tourism destinations, popularly known as the homestay village. It has created its identity as a cultural homestay tourism on the way to Annapurna circuit. The community homestay tourism has contributed a remarkable footstep in the local tourism arena. This study has tried to put some efforts on the homestay sector that could play pivotal roles for the further researchers, scholars and students of tourism discipline. It has tried to identify the changes brought in economy in the community by homestay tourism promotion. It focuses on the impacts of homestay by analyzing the factors viz. employment opportunities, changes in income, development of infrastructures, fund generation for communal activities and micro-entrepreneurship. These factors are considered as the variables for the study. Further, it tries to establish a comparative relationship between establishment of homestay as a cause and women empowerment as the effect.